Pengukuran Kinerja Marketing Mix Dan Perumusan Srategi Pemasaran Ukm Batik Pamekasan (Studi Kasus: UKM Batik Kec. Proppo Kab. Pamekasan) - Kukuh Winarso; Imam Al-Farisyi (Universitas Airlangga, 2015)
This research is to find out the marketing on marketing mix and formulating marketing strategies for development of the UKMBatik Pamekasan to be able to compete with other products.The analysis used in this research are importance performance analysis used to measure the marketing mixed on consumer perceptions, PGCV index used to determine the priority scale of marketing mixed and SWOT analysis used to formulating marketing strategies UKMBatik Pamekasan.This research result indicates that the variables product in consumer expectations that the quality of the product batik, a coloring material and subtle product batik.In variable price in the hope that the consumer products already satisfy customers. In variable promotion, consumers were unsatiable for UKM based on variables place it was amazed at the ease of getting people in product markets. Based on the analysis SWOT acquired marketing strategy on UKMBatik Pamekasan namely by increasing the quality of the people to gain market share of broader at home and globally, the government is helping UKM batik to improve product promotion out the land to use the market to provide a bargain price based on the economy condition and to improve relations with the public servants/governance institutions in order to keep consumer products batik Pamekasan.